Enterocyte-Based Bioassay via Quantitative Combination of Proinflammatory Sentinels Specific to 8-keto-trichothecenes - Park, Seong-Hwan; Moon, Yuseok (Frontiers in Immunology, 2020)
Type B 8-keto-trichothecenes are muco-active mycotoxins that exist as inevitable contaminants in cereal-based foodstuffs. Gut-associated inflammation is an early frontline response during human and animal exposure to these mycotoxins. Despite various tools for chemical identification, optimized biomonitoring of sentinel response-associated biomarkers is required to assess the specific proinflammatory actions of 8-keto-trichothecenes in the gut epithelial barrier. In the present study, intoxication with 8-keto-trichothecenes in human intestinal epithelial cells was found to trigger early response gene 1 product (EGR-1) that plays crucial roles in proinflammatory chemokine induction. In contrast, epithelial exposure to 8-keto-trichothecenes resulted in downregulated expression of nuclear factor NF-kappa-B p65 protein, a key transcription factor, during general inflammatory responses in the gut. Based on the early molecular patterns of expression, the inflammation-inducing activity of 8-keto-trichothecenes was quantified using intestinal epithelial cells with dual reporters for EGR-1 and p65 proteins. EGR-1-responsive elements were linked to luciferase reporter while p65 promoter was bound to secretory alkaline phosphatase (SEAP) reporter. In response to conventional inflammagens such as endotoxins and cytokines such as TNF-, both luciferase and SEAP activity were elevated in a dose-dependent manner. However, as expected from the mechanistic evaluation, 8-keto-trichothecene-exposed dual reporters of luciferase and SEAP displayed contrasting expression patterns. Furthermore, 8-keto-trichothecene-elevated EGR-1-responsive luciferase activity was improved by deficiency of PSMA3, an alpha-type subunit of the 20S proteasome core complex for ubiquitin-dependent EGR-1 degradation. This molecular event-based dual biomonitoring in epithelial cells is a promising supplementary tool for detecting typical molecular inflammatory pathways in response to 8-keto-trichothecenes in the food matrix.